Fatal fulminant Clostridioides difficile colitis caused by Helicobacter pylori eradication therapy; a case report. Issue 3 (March 2020) - Nei, Takahito; Hagiwara, Jun; Takiguchi, Toru; Yokobori, Shoji; Shiei, Kim; Yokota, Hiroyuki; Senoh, Mitsutoshi; Kato, Haru
Abstract: A 74-year-old male was referred to our critical care department for refractory severe watery diarrhea with advanced leukocytosis (over 70, 000/μl) after multiple administrations of eradication therapy against Helicobacter pylori (HP). He was diagnosed as having fulminant colitis due to Clostridioides difficile after antimicrobial eradication therapy. He was given intravenous metronidazole and oral vancomycin. He also received supportive therapy including continuous hemodiafiltration for severe metabolic acidosis. However, despite emergency open sigmoidectomy, he died. The C. difficile isolate recovered was PCR-ribotype 002, which was positive for toxins A and B but negative for binary toxin. HP eradication therapy for prevention of chronic gastritis and stomach cancer is now in widespread use. Although such secondary severe complications are rare, we consider it to be necessary to pay sufficient attention when administering HP eradication therapy.